Trace Element Composition of Placer Gold Across the Okanagan Fault, Kelowna, British Columbia, Canada - Greenough, John; Tetland, Mikkel (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2023)
For 100 years, placer gold has been important to the settlement, economic development, and, recently, recreational geology of the Kelowna, British Columbia, area. It is best-known to occur in modern-day, Mission Creek and Lambly Creek sedimentary rocks, as well as a paleoplacer occurrence in Miocene sediments of the historical Winfield mine. The Mission Creek and Winfield localities are east of the west-dipping, low-angle, normal Okanagan Fault, which has been active since the Eocene. Lambly Creek is west of the fault. Late Paleozoic to Eocene igneous and metasedimentary rocks occur in the Lambly Creek catchment but Eocene gneiss units, unroofed by the fault, occur on the Okanagan Valley’s east side. This study tests the hypothesis that native placer gold compositions vary across the Okanagan Fault reflecting different sources and histories for the gold. A modest number of Au and Ag analyses (23 analyses) in usefully representative placer gold samples were determined on a scanning electron microscope with an energy dispersive spectrometer (SEM-EDS). Spots analyzed for Au and Ag were also analyzed for 19 trace elements using laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Mercury was semi-quantitatively determined in ‘unknown’ gold grains by first estimating its concentration (~3.69 ppm) in the AuRM2 external standard. Proportions of Au:Ag:Cu in grain cores indicate all the gold came from mesothermal/hypogene or possibly Au porphyry bedrock deposits though primary signatures may have been obscured by metamorphism or weathering. Winfield and Mission Creek grains tend to have higher siderophile Fe, Ni, Pd and Pt and chalcophile elements As, Se, Te, Hg, Pb and Bi but lower Cu and Sb concentrations than Lambly Creek gold. Mercury is distinctly higher in Winfield and Mission Creek gold than in Lambly Creek gold from the west side of the valley; the element appears particularly useful for ‘fingerprinting’ gold. Lambly Creek gold compositions indicate derivation from two orogenic/hypogene sources from greenstone and plutonic/hydrothermal rocks present in the catchment area. Modern day Mission Creek and Miocene paleoplacer Winfield grains have a similar hypogene trace element signature but there are no known local bedrock gold sources. The Mission Creek and Winfield gold grain cores are surrounded by < 10 µm, Au-rich, Ag- and trace element-poor, rims. Lambly Creek grains lack such rims. The Au-rich rims on modern day Mission Creek and Miocene Winfield gold may reflect prolonged near-surface exposure with surficial electrochemical dissolution of hypogene trace elements or the biological precipitation of gold. Low Ag and red colouration on the surface of grains support the biological precipitation hypothesis. The shared trace element signature, together with the Au-rich rims indicate that modern day placer gold in Mission Creek was multiply reworked from Miocene paleoplacers similar to the Winfield occurrence as a result of uplift and erosion of rocks on the east side of Okanagan Fault.